The distribution of power among corporate managers, shareholders, and directors - Jensen, Michael C.; Warner, Jerold B. (Journal of Financial Economics, 1988)
This article surveys the seventeen papers in this special issue of the Journal of Financial Economics, and related work. The major findings are: (1) patterns of stock ownership by insiders and outsiders can influence managerial behavior, corporate performance, and stockholder voting in election contests; (2) corporate leverage, inside stock ownership by managers, and the control market are interrelated; (3) departures from one share/one vote affect firm value and efficiency; (4) takeover resistance through defensive restructurings or poison pill provisions is associated with declines in share price; and (5) top management turnover is inversely related to share price performance.